2021
DOI: 10.1186/s40824-021-00220-y
|View full text |Cite
|
Sign up to set email alerts
|

A novel gelatin/chitooligosaccharide/demineralized bone matrix composite scaffold and periosteum-derived mesenchymal stem cells for bone tissue engineering

Abstract: Background A novel biodegradable scaffold including gelatin (G), chitooligosaccharide (COS), and demineralized bone matrix (DBM) could play a significant part in bone tissue engineering. The present study aimed to investigate the biological characteristics of composite scaffolds in combination of G, COS, and DBM for in vitro cell culture and in vivo animal bioassays. Methods Three-dimensional scaffolds from the mixture of G, COS, and DBM were fabri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 24 publications
3
15
0
Order By: Relevance
“…Unlike mineralization, the maximum ALP activity in osteogenic differentiation media was relatively similar for each cell type, albeit more transient, with all cell types reaching a similar level, although at different time points. This is consistent with previous studies, which have demonstrated transient levels of ALP activity on scaffolds, with levels increasing at one time‐point but then subsequently decreasing 29–33 . Overall, in terms of viability, ALP activity, and mineralization assays, the data strongly supports BMSCs, ADSCs, and CHSCs as promising candidates for successful in vivo bone healing with the SMP scaffold.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Unlike mineralization, the maximum ALP activity in osteogenic differentiation media was relatively similar for each cell type, albeit more transient, with all cell types reaching a similar level, although at different time points. This is consistent with previous studies, which have demonstrated transient levels of ALP activity on scaffolds, with levels increasing at one time‐point but then subsequently decreasing 29–33 . Overall, in terms of viability, ALP activity, and mineralization assays, the data strongly supports BMSCs, ADSCs, and CHSCs as promising candidates for successful in vivo bone healing with the SMP scaffold.…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with previous studies, which have demonstrated transient levels of ALP activity on scaffolds, with levels increasing at one time-point but then subsequently decreasing. [29][30][31][32][33] Overall, in terms of viability, ALP activity, and mineralization assays, the data strongly supports BMSCs, ADSCs, and CHSCs as promising candidates for successful in vivo bone healing with the SMP scaffold.…”
Section: Discussionmentioning
confidence: 81%
“…In a review paper, titanium surfaces functionalized with chitosan were concluded to have greater osseointegration capacity than uncoated controls [27]. Thitiset et al [28], used chitoologosaccharide for preparation of composites that did show promising results in cell culture, as well as for new bone formation in vivo. The results from Thitiset et al are remarkable in the light of our ideas on the mechanism of action of chitosan in bone regeneration where chitooligosachharides play a central role [17].…”
Section: Discussionmentioning
confidence: 99%
“…The scaffold triggered the proliferation and differentiation of osteoblast cells and proved to be an efficient bone graft with excellent osteogenic potency for bone tissue engineering applications. 66 Chitosan. Chitosan is a polysaccharide that is extracted by deacetylation of chitin.…”
Section: Polymers Used In Electrospinningmentioning
confidence: 99%